The new era of aspiration risk: The dilemma of GLP-1 receptor agonists - Jack Madden; Andrew Goyen (Journal of Perioperative Nursing)
There is a new wave of aspiration risk heading towards our operating theatres in the coming years. The popular weight loss drugs, glucagon-like peptide (GLP-1) receptor agonists, are providing us with new dilemmas in fasting guidelines and airway management. What does the anaesthetic team need to know?